2016
DOI: 10.1148/radiol.2015141779
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis: Assessment with Acoustic Structure Quantification of US Imaging

Abstract: ).q RSNA, 2015 Purpose:To investigate the diagnostic performance of acoustic structure quantification (ASQ) for the assessment of hepatic steatosis by using hydrogen 1 ( 1 H) magnetic resonance (MR) spectroscopy as the reference standard and to compare ASQ with hepatorenal ratio. Materials andMethods:This prospective study was approved by an institutional review board, and informed written consent was obtained from all participants. ASQ and MR spectroscopy were performed in 89 participants (mean age, 41.48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 28 publications
(33 reference statements)
2
54
1
1
Order By: Relevance
“…Our results also show that US-SWE is essentially independent of liver fat content. Other new techniques, such as acoustic structure quantification, which were not used in our study, have been reported to serve as quantitative biomarkers, at least in subjects with clinically significant steatosis [52]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results also show that US-SWE is essentially independent of liver fat content. Other new techniques, such as acoustic structure quantification, which were not used in our study, have been reported to serve as quantitative biomarkers, at least in subjects with clinically significant steatosis [52]. …”
Section: Discussionmentioning
confidence: 99%
“…This CAP technique is performed in conjunction with liver fibrosis assessment based on 1D Transient Elastography (Foucher et al 2006b, Sandrin et al 2002. Other recent studies have used ultrasound to detect steatosis (Lin et al 2015, Son et al 2015 but they are based on a single cutoff value. Beyond such binary below/above diagnosis, there is a real clinical unmet need for a non-expensive, widely available, and highly reliable technique to precisely grade hepatic steatosis as MRI does.…”
Section: Introductionmentioning
confidence: 99%
“…Medical imaging has progressed rapidly in recent years. Several noninvasive methods have been developed for quantification of fat content, one of those is acoustic structure quantification of ultrasonography, which allows detection of hepatic steatosis that is 10% or greater in living liver donors [5]. This new technique has increased sensitivity in quantification of hepatic steatosis [6]; but there is still need for more precise quantification for living donor selection.…”
mentioning
confidence: 99%